THE ROLE AND SIGNIFICANCE OF THE GROSS DOMESTIC PRODUCT IN ENSURING MACROECONOMIC STABILITY IN THE ECONOMY OF OUR COUNTRY (Marketing Journal, 2026)
This article analyzes the role and significance of Gross Domestic Product (GDP) in ensuring macroeconomic stability. The study examines GDP as the main indicator of economic growth, its structure, and dynamic changes in assessing a countryʼs economic potential. Furthermore, the interrelation between GDP growth rates and macroeconomic equilibrium, as well as the effects of inflation, employment, investment, and the trade balance on GDP, are discussed through economic analysis. The article provides an analytical overview of Uzbekistanʼs GDP growth trends in recent years based on empiric al data, identifying the main factors influencing sustainable economic development. The results highlight the importance of enhancing GDP through innovation, increasing production efficiency, and implementing digital technologies to strengthen macroeconomi c stability.
Keywords: Gross Domestic Product; macroeconomic stability; economic growth; inflation; investment; employment; innovative development